If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 3x = 4 + x Solving -6 + 3x = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -6 + 3x + -1x = 4 + x + -1x Combine like terms: 3x + -1x = 2x -6 + 2x = 4 + x + -1x Combine like terms: x + -1x = 0 -6 + 2x = 4 + 0 -6 + 2x = 4 Add '6' to each side of the equation. -6 + 6 + 2x = 4 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = 4 + 6 2x = 4 + 6 Combine like terms: 4 + 6 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| x=-3*y | | a=49+6a | | 517=33+22w | | 23=-7n-3(1+2n) | | x/56= | | mx+na-nx=ma | | -31u=-992 | | x*56= | | x^2-6x-4y+40y=95 | | y=1/4(-4)-3 | | 5(-8m-1)=-45 | | b-3=9b+53 | | 3b-2/3=b-3/6 | | 6=x-3+7 | | -6=1+x-8x | | 6x-5=5x-1 | | 5x+13=13-8x | | 4.59+x=4.67 | | 3(2y-4)+2y+2=2y+7+y+8 | | a=49-6a | | 6x+1y=0 | | 16.31+x=22.12 | | 14x+10=9+-3x | | (Y+3)(y-4)= | | 1-7c-7c=15 | | 8.09+x=9.7 | | 6x+4+2x-6=5(x-2)+2x+6-x | | X^2-4y^2-6x+40y-95=0 | | y=23.1(492.3) | | -2=-18+r | | 3y+1=5y-7(2) | | 1=u/9-4 |